Hypoglycemic Effects of Lycium barbarum Polysaccharide in Type 2 Diabetes Mellitus Mice via Modulating Gut Microbiota - Ma, Qingyu; Zhai, Ruohan; Xie, Xiaoqing; Chen, Tao; Zhang, Ziqi; Liu, Huicui; Nie, Chenxi; Yuan, Xiaojin; Tu, Aobai; Tian, Baoming; Zhang, Min; Chen, Zhifei; et al. (Frontiers in Nutrition, 2022)
This study aims to explore the molecular mechanisms of lycium barbarum polysaccharide (LBP) in alleviating type 2 diabetes by modulation of intestinal flora. Diabetic animal model was induced by high-fat-diet (HFD) combined with streptozotocin (STZ). Results indicated that LBP effectively alleviated the symptoms of hyperglycemia, hyperlipidemia, and insulin resistance in diabetic mice. High dosage of LBP exerted better hypoglycemic effects than LBP with low and medium dosage. LBP markedly increased the activities of CAT, SOD, and GSH-Px, mitigated inflammation of diabetic mice. The analysis of 16S rDNA disclosed that LBP notably restored the composition of intestinal flora, e.g., increased the relative abundance of Bacteroides, Ruminococcaceae_UCG-014, Intestinimonas, Mucispirillum, Ruminococcaceae_UCG-009, decreased Allobaculum, Dubosiella, Romboutsia. In line with the increase of beneficial genus, LBP significantly increased the production of short chain fatty acids (SCFAs) of diabetic mice. The up-regulated expression of PYY, GLP-1, and insulin were remarkedly reversed by LBP in diabetic mice. The RT-qPCR analysis illustrated that LBP distinctly regulated the glucose metabolism of diabetic mice by activating the IRS/PI3K/AKT signals pathway. These results indicated that LBP effectively alleviated the hypoglycemia and hypolipidemia of diabetic mice by the modulation of intestinal flora.